Mov10 suppresses retroelements and regulates neuronal development and function in the developing brain - Skariah, Geena (BMC Biol, 2017)
BACKGROUND: Moloney leukemia virus 10 (Mov10) is an RNA helicase that mediates access of the RNA-induced silencing complex to messenger RNAs (mRNAs). Until now, its role as an RNA helicase and as a regulator of retrotransposons has been characterized exclusively in cell lines. We investigated the role of Mov10 in the mouse brain by examining its expression over development and attempting to create a Mov10 knockout mouse. Loss of both Mov10 copies led to early embryonic lethality. RESULTS: Mov10 was significantly elevated in postnatal murine brain, where it bound retroelement RNAs and mRNAs. Mov10 suppressed retroelements in the nucleus by directly inhibiting complementary DNA synthesis, while cytosolic Mov10 regulated cytoskeletal mRNAs to influence neurite outgrowth. We verified this important function by observing reduced dendritic arborization in hippocampal neurons from the Mov10 heterozygote mouse and shortened neurites in the Mov10 knockout Neuro2A cells. Knockdown of Fmrp also resulted in shortened neurites. Mov10, Fmrp, and Ago2 bound a common set of mRNAs in the brain. Reduced Mov10 in murine brain resulted in anxiety and increased activity in a novel environment, supporting its important role in the development of normal brain circuitry. CONCLUSIONS: Mov10 is essential for normal neuronal development and brain function. Mov10 preferentially binds RNAs involved in actin binding, neuronal projection, and cytoskeleton. This is a completely new and critically important function for Mov10 in neuronal development and establishes a precedent for Mov10 being an important candidate in neurological disorders that have underlying cytoarchitectural causes like autism and Alzheimer’s disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12915-017-0387-1) contains supplementary material, which is available to authorized users.